Spectral urbanism - Collins, Tom; Douglas, Andrew (Interstices: Journal of Architecture and Related Arts, 2023)
Responding to the clearing in the 1970s of an estimated 15,000 houses to make way for the Central Motorway Junction in Tāmaki Makaurau Auckland, this research project presents a speculative architectural proposal for a wallpaper archive and a pedestrian bridge to a traffic island of regenerating trees at the centre of Grafton Gully. The wallpaper archive—intended to house a modest historic wallpaper collection by local heritage architects Salmond Reed Architects—and the bridge are cover for a larger recovery of historical significance eclipsed by the transport infrastructure. The architecture proposed intends both memorial and future-building functions and arises out of an investigation of practice-led processes centred on casting, modelling, printing, and photography. In doing so, this creative design research demonstrates a form of architectural renovation as storytelling, in which the past is recalled not through material restoration, but re-narrativisation—a process I have come to call spectral urbanism.